ANALISIS FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BEI PERIODE 2013-2016 - Chika Audy Rahmaning Wijaya, 15.05.62.0009; Wardjono, Wardjono (Students' Journal of Accounting and Banking, 2018)
This study examines the factors that affect the value of companies in banking companies listed on the IDX period 2013-2016. This research is conducted in Bursa Efek Indonesia by using unit of analysis of banking company.Sampling method using purposive sampling, that is sample determination technique by using certain criteria. The relationship or influence between variables is explained by using multiple linier regression analysis method and hypothesis test (t test). The results of this study indicate that Net Interest Margin (NIM), Capital Adequacy Ratio (CAR) and Price Earning Ratio (PER) has a positive effect is significant, Loan to Deposit Ratio (LDR) has a significant negative effect is significant, Good Corporate Governance and firm growthhas not a significant effect on firm value. Keywords:Price to Book Value,Loan to Deposit Ratio, Good Corporate Governance, Net Interest Margin, Capital Adequacy Ratio,firm growth, Price Earning Ratio.